Multi-walled carbon nanotubes composited with nanomagnetite for anodes in lithium ion batteries. Issue 10 (6th February 2015) - Li, Xiaoyu; Gu, Hongbo; Liu, Jiurong; Wei, Huige; Qiu, Song; Fu, Ya; Lv, Hailong; Lu, Guixia; Wang, Yiran; Guo, Zhanhu
<x xml:space="preserve">Abstract</x> The multi-walled carbon nanotube (MWNT) nanocomposites with homogenously anchored nanomagnetite of 10–20 nm prepared by a hydrothermal-annealing method exhibit excellent performances as anode materials for lithium ion batteries.